2016
DOI: 10.7860/jcdr/2016/18837.7755
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of GeneXpert with ZN Stain and Culture in Samples of Suspected Pulmonary Tuberculosis

Abstract: GeneXpert has a higher sensitivity than AFB smear microscopy in respiratory samples. GeneXpert can be a useful tool for early diagnosis of patients with high clinical suspicion of pulmonary tuberculosis. Positive GeneXpert, but culture negative results should be read cautiously and be well correlated with clinical and treatment history of the patient. The other major advantage of Gene Xpert is that it simultaneously detects Rifampicin resistance and especially beneficial in patient with MDR and HIV associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
109
2
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(134 citation statements)
references
References 19 publications
19
109
2
4
Order By: Relevance
“…Furthermore, Singh et al, 2016, demonstrated a sensitivity of 100% and specificity of 100% for pulmonary samples by using GeneXpert assay. In addition, Agrawal et al, 2016, reported that the sensitivity and specificity of GeneXpert in sputum were 100% and 90% that is compatible with the study of Sharma et al, 2015who found a sensitivity of 96.9% and a specificity of 99.8%.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…Furthermore, Singh et al, 2016, demonstrated a sensitivity of 100% and specificity of 100% for pulmonary samples by using GeneXpert assay. In addition, Agrawal et al, 2016, reported that the sensitivity and specificity of GeneXpert in sputum were 100% and 90% that is compatible with the study of Sharma et al, 2015who found a sensitivity of 96.9% and a specificity of 99.8%.…”
Section: Resultssupporting
confidence: 78%
“…Similar results were demonstrated by Agrawal et al, 2016, Bajrami et al, 2016 and Tang et al, 2017. This discordance between GeneXpert and MGIT culture was also reported by Agrawal et al, 2016 found that 9,6and 19 samples were GeneXpert positive and culture negative respectively. Also, the same previous authors found that 2, 2 and 13 samples were negative by GeneXpert and positive by culture respectively.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Similar results of very high sensitivity of CBNAAT in smear positive cases have been reported by most of the studies, but sensitivity of CBNAAT in smear negative cases varied between 35%-79.1% among several studies [ Table 5]. [12,15,[16][17][18][19][20] Specificity of CBNAAT was 100% (95% CI-92.89%-100%) in this study in both smear positive and smear negative group and is in line with other studies which have also demonstrated a very high specificity of CBNAAT in diagnosis of pulmonary tuberculosis [ Table 5]. [12,15,[16][17][18][19][20] Sensitivity of sputum smear microscopy was even lower in this study in patients infected with HIV, all of the TB-HIV co-infected patients were sputum smear negative in comparison to 38 out of 195 immunocompetent patients being sputum smear-positive on microscopy (p-0.01).…”
Section: Discussionsupporting
confidence: 72%